Health And Social Status Of Senior Citizens In Rural Areas - Lal, Sunder; Mohan, Brij; Punia, M S (Indian Journal of Community Health, 1997)
Research Problem: What is the quality of life of the elderly people, as also the available support system, in rural areas? Objectives:i) To determine the demographic profile of elderly ii) To assess the socio-economic, nutritional, health, morbidity and dependency status, and health care utilization. Study Design: Population based cross sectional study. Setting: Community Development Block - Lakhanmajra Participants: Persons above the age of 65 years. Sample Size: 809 elderly above the age of 65 years. Study Variables: Demographic profile, Literacy, Occupation, Health, Nutrition, Mobility, Dependency, Substance abuse, Support system. Statistical Analysis: By simple proportions. Result: In this study, majority ofthe elderly were self reliant and mobile, being an asset to the family and led socially useful and productive lives. Their predominant problems were visual impairment, joint pains, respiratory diseases and hearing impairment. Joint family and government pension was the major support system to the elderly. However, there is an imperative need to organize education, training and special service programmes for the elderly at the village level.